Analysis Of Dividend Policy in Companies Listed on The Indonesia Stock Exchange - Dahlia Br Pinem; Bernadin Dwi M; Munasiron Miftah; Marlina Tanjung; Nani Ariani (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The research objective is to analyze the effect of liquidity, leverage, and profitability on a dividend policy. The objects used are companies listed on the Indonesia Stock Exchange in 2018-2020. The sampling technique used is purposive sampling. Based on the predetermined criteria, the sample obtained was 117 companies in the observation period for three years, thus in this study using 351 sample data were obtained. The dependent variable is dividend policy using the Dividend Payout Ratio (DPR), instead, the independent variable includes liquidity using the Current Ratio (CR), leverage measurements using the Debt-to-Equity Ratio (DER), and also profitability using Return on Equity (roe). The data in the study was then analyzed using the data regression analysis panel assisted by the E-Views 12 program which has a significance level of 5%. The results have shown that (1) liquidity does not affect dividend policy, (2) leverage has an effect on dividend policy, and (3) profitability has an influence on dividend policy.